Caring for the soul in a postmodern age : politics and phenomenology in the thought of Jan Patočka - Findlay, Edward F., 1965- (State University of New York Press, 2002)
"In 1977 the sixty-nine-year-old Czech philosopher Jan Patocka died from a brain hemorrhage following a series of interrogations by the Czechoslovak secret police. A student of Husserl and Heidegger, he had been arrested, along with young playwright Vaclav Havel, for publicly opposing the hypocrisy of the Czechoslovak Communist regime. Patocka had dedicated himself as a philosopher to laying the groundwork of what he termed a "life in truth."" "This book analyzes Patocka's philosophy and political thought and illuminates the synthesis in his work of Socratic philosophy and its injunction to "care for the soul." In bridging the gap, not only between Husserl and Heidegger, but also between postmodern and ancient philosophy, Patocka presents a model of democratic politics that is ethical without being metaphysical, and transcendental without being foundational."--Jacket